An Overview On The Growth Of Halal-Concept Hotel Chain’s Industry In Malaysia - Ahmad amir; Tasnim Abdul Rahman (ASEAN Journal of Halal Study, 2024)
The paper attempts to survey the emergence of halal-concept hotel chain in Malaysia by reviewing current project and initiative to set up the blueprint and framework of halal-concept hotel based on the principle of halalan toyyiban (allowed and permissible for consumption). Against this backdrop, it looks into current perception and effort to develop shariah-based hotel network and to conceptualize the idea into dynamic embodiment of contemporary Islamic market that reflect a major breakthrough in the industry and marked an important achievement in the halal-business enterprise and current direction of Islamic tourism in Malaysia. The aim of this research is to highlight the significant growth of halal-concept hotel in Malaysia by outlining its origin, conceptual framework and practical orientation, standard practice and basic operation, principal guideline and ethical vision in managing the business, and significant achievement and future challenge and prospect. The study is based on qualitative (narrative) and quantitative (inventories) methods where data is collected from intensive library research and fieldwork. From the discussion, the finding shows that the industry has been targeting to become an alternative to conventional hotel and improving the conventional order and practice of hospitality in line with shariah-based principle, by invoking a Muslim-friendly environment and embark on projecting new innovation to advance Islamic alternative as Malaysia continue to lead this highly competitive market of global halal industry.